Psychometric properties and item response theory analysis of the Persian version of the social pain questionnaire - Sepehrinia, Mahya; Farahani, Hojjatollah; Watson, Peter; Amini, Nasim (Frontiers in Psychology, 2024)
Social pain is an emotional reaction which is triggered by social exclusion or ostracism and has been extensively investigated in the literature. The Social Pain Questionnaire (SPQ) is the only scale for measuring social pain as a dispositional factor. The current study aimed at examining the psychometric properties of the Persian version of the SPQ (N = 400), as well as the convergent and divergent validity. The SPQ's unidimensionality was affirmed by confirmatory factor analysis (CFA) and its internal consistency was robust. The correlation between this scale and the following measures endorsed its divergent and convergent validity: Self-esteem, Perceived Social Support, and Interpersonal Sensitivity. Finally, Item Response Theory Analysis emphasized the effectiveness of SPQ items in discerning various levels of social pain. Therefore, the Persian SPQ stands as a reliable and valid measure of social pain, with the potential to stimulate further research in the field.